Evaluación de la planta de tratamiento de aguas residuales del AyA en la urbanización Las Lomas de Buenos Aires, Puntarenas. - Jiménez-Gonzáles, Susana (Instituto Tecnológico de Costa Rica, 2014)
The Instituto Costarricense de Acueductos y Alcantarillados has a wastewater treatment plant for “Las Lomas” urbanization in Buenos Aires, Puntarenas. This plant is a single facultative pond which presents microalgae overproduction that generates a reduction in the effluent quality, causes operational problems and also does not comply with the national legislation. Therefore, current facultative pond was evaluated by major design parameters for facultative ponds, to recommend a potential solution for improvement to optimize the treatment of wastewater. Evaluation of the current facultative pond, based on average daily flow of 40 m3/day and 50 m3/day maximum daily, resulted in major problems, such as, L/A ratio, the surface loading rate and, most importantly, the detention time. Subsequently, the actual area required for treatment of this wastewater was calculated, based on the maximum daily flow, is 725 m2. Then, different scenarios were evaluated in the same way. It was evaluated: two ponds in series (the first facultative and the second one a maturation pond); two ponds in series (the first facultative and the second a macrophyte pond) and three ponds (two facultative in parallel and one a maturation pond). Then, was calculated the approximate cost to implement these proposal (including all costs of removing sludge, lagoon waterproofing, structural work, mechanical installation and other indirect and additional costs), which resulted in required an investment of $78.400,00; $118.300,00 y $90.100,00 for the proposals 1, 2 and 3, respectively. When evaluating all alternatives from a technical, environmental and economic point of view, the proposal is recommended to upgrade the system by using two ponds in series (the first facultative and the second one a maturation pond) instead of the existing one.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2014.
Keywords: Microalgas; Ultrasonido; Lagunas; Optimización; Alcantarillas; Bioquimica